Autekologi dan Pemanfaatan Buah Untit (Nephelium maingayi Hiern) oleh Suku Dayak Ngaju Kalimantan Tengah - Dini Pujiarti; Gunawan Gunawan; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2021)
Indonesia is a country with diverse genetic resources (SDG) of tropical fruits, this study aimed to provide information about Untit fruit including environmental factors associated with this fruit (Nephelium maingayi), and utilization of the Untit fruit plant by the Dayak Ngaju tribe in Cempaga District, Kotawaringin Timur Regency, Central Kalimantan. The data used in this study were primary data and secondary data. Primary data collection was carried out by field observation and semi-structured interviews using a questionnaire. Secondary data is the result of literature studies from various libraries to support primary data. Environmental parameters (air temperature, humadity, soil pH, soil temperature, altitude and distance from water sources) in the field were analysis using Principal Component Analysis (PCA). The result of analysis showed that the most influential enviromental factor Untit fruit plants was air temperature. The plant was used as table fruit, medicine and building materials. In addition, the fruit plant Untit is used by the Dayak Ngaju tribes as a medicine for stomach aches (dysentery), medicine for wounds, rashes, pimples and ulcers. The most widely used parts of the plant were fruit, leaves, stems and bark.